Evaluation of Genetic Diversity of Seedling Raised Pecan Nut (Carya illinoensis K.) for Tree Growth Habit - Thakur, Kiran; Sharma, Girish; Sajwan, Paramjeet; Deepika; Prasad, Heerendra (International Journal of Economic Plants, 2019)
The present investigation entitled evaluation of diversity for tree growing habit in seedling raised pecan nut [Carya illinoensis (Wang) K. Koch] was carried out to document the available genetic variability in pecan nut germplasm and to select elite pecan nut genotypes possessing superior attributes and quality traits. During the study, data was recorded on seventy pecan nut trees growing in experimental field orchard of Department of Fruit science YSPUHF, Nauni, Solan (HP). Remarkable variability was observed in seedling pecan nut trees for tree growth characters viz., tree growth habit, density of branching and shoot colour of one year old shoot. In this study 12 (17.14%) seedlings had upright growth habit, 33 (47.14%) were semi-upright and 25 (35.72%) were of spreading growth habit. 5 (7.14%) seedling trees possessed sparsely dense branching, 32 (45.72%) exhibited medium and 33 (47.14%) had highly dense branching. Twenty six (37.14%) seedling trees possessed greenish brown colour of one year old shoot, 38 (54.29%) had medium brown and 6 (8.57%) had reddish brown colour of one year old shoot.